Body knowledge and control : studies in the sociology of physical education and health - Evans, John, 1952 October 16-; Davies, Brian, 1938-; Wright, Jan, 1948- (Routledge, 2004)
Drawing together some of the latest research on the body and schooling, Body Knowledge and Control offers a sharp and challenging critique of (post) modern day attitudes toward obesity, health, childhood and the mainstream science and business.